Biodegradable Green Composites: Effects of Potassium Permanganate kmno4 Treatment on Thermal, Mechanical, and Morphological Behavior of Butea Parviflora (Bp) Fibers - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study emphasizes the importance of utilizing biodegradable material Butea parviflora (BP) fiber for sustainable solutions. BP fiber offers numerous ecological benefits, such as being lightweight, biodegradable, and affordable to recycle. The study examines the effects of potassium permanganate (KMnO4) treatment on BP fiber and analyzes its physical and chemical behavior using various methods, including X-ray Diffraction (XRD) analysis, tensile testing, thermogravimetric analysis, thermal conductivity, Scanning Electron Microscopy (SEM), and Fourier Transform Infrared spectroscopic (FTIR) analysis. The results demonstrate that BP fiber possesses low density (1.40 g/cc) and high cellulose content (59.4%), which fosters compatibility between the matrix and resin. XRD analysis indicates a high crystallinity index (83.47%) and crystallite size (6.4 nm), showcasing exceptional crystalline behavior. Treated fibers exhibit improved tensile strength (198 MPa) and Young’s modulus (4.40 GPa) compared to untreated fibers (tensile strength—92 MPa, tensile modulus—2.16 GPa). The Tg-DTA thermograms reveal the fiber’s thermal resistance up to 240 °C with a kinetic activation energy between 62.80–63.46 KJ/mol. Additionally, the lowered thermal conductivity (K) from Lee’s disc experiment suggests that BP fiber could be used in insulation applications. SEM photographic results display effective surface roughness for composite making, and FTIR studies reveal vibrational variations of cellulosic functional groups, which correlates with increased cellulosic behavior. Overall, the study affirms the potential of BP fiber as a reinforcing material for composite-making while emphasizing the importance of utilizing biodegradable materials for sustainability. © 2023 by the authors.